2016
DOI: 10.5306/wjco.v7.i1.106
|View full text |Cite
|
Sign up to set email alerts
|

Role of copper transporters in platinum resistance

Abstract: Platinum (Pt)-based antitumor agents are effective in the treatment of many solid malignancies. However, their efficacy is limited by toxicity and drug resistance. Reduced intracellular Pt accumulation has been consistently shown to correlate with resistance in tumors. Proteins involved in copper homeostasis have been identified as Pt transporters. In particular, copper transporter receptor 1 (CTR1), the major copper influx transporter, has been shown to play a significant role in Pt resistance. Clinical studi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
67
0
1

Year Published

2016
2016
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 104 publications
(71 citation statements)
references
References 74 publications
3
67
0
1
Order By: Relevance
“…Increased CTR1 expression by the cells results in an increased platinum concentration and decreased resistance to cisplatin . Combination of platinum drugs with bortezomib, a modulator for copper transporter expression, is a current option for platinum‐resistant solid tumors …”
Section: Multiple Drug Resistancementioning
confidence: 99%
“…Increased CTR1 expression by the cells results in an increased platinum concentration and decreased resistance to cisplatin . Combination of platinum drugs with bortezomib, a modulator for copper transporter expression, is a current option for platinum‐resistant solid tumors …”
Section: Multiple Drug Resistancementioning
confidence: 99%
“…Recently reviewed results also strongly suggest more complex mechanisms involved in this cytotoxicity, such as the interaction with mitochondria and with the immunologic tumour environment [4]. Several resistance mechanisms have been proposed to be involved in a decreased clinical response to platinum derivatives, such as modified expression of membrane copper transporters [5], increased inactivation of intracellular platinum derivatives by glutathione [6], defects in the apoptotic machinery [7] or increased repair activity on the DNA adducts [8,9].…”
Section: Introductionmentioning
confidence: 99%
“…Studies have reported that several transporters have different functions to regulate the net intracellular level of platinum drugs [24, 25]. Evidence has indicated that copper transporters have a crucial role in transporting platinum drugs into cells [8, 26]. The major copper influx transporter hCtr1 has been reported to assist the uptake of CDDP, carboplatin, and oxaliplatin and to regulate their cytotoxicity in yeast and mammalian cells [27, 28].…”
Section: Discussionmentioning
confidence: 99%